Pharmacological, behavioral, and sociocultural dimensions of GLP-1 and dual incretin therapies in Saudi Arabia: clinical evidence, misuse patterns, and policy priorities - Aloufi, Lamar K.; Almaysari, Renas Khalid; Aljehani, Abdullah T.; Mohammed D., Almalki Dhaifallah; Alnefaie, Zayed Mohammed (International Journal of Basic & Clinical Pharmacology, 2025)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dual incretin therapies, including semaglutide and tirzepatide, have reshaped the management of obesity and type 2 diabetes. Their rapid uptake in Saudi Arabia has created both opportunities and challenges, notably the rise in cosmetic-driven use, socioeconomic disparities, and emerging regulatory concerns. This narrative review synthesizes clinical, mechanistic, sociocultural, and policy-related evidence on GLP-1 and dual incretin therapies in Saudi Arabia, with a particular focus on real-world use patterns, misuse, and implications for Vision 2030 health goals. Evidence was drawn from randomized clinical trials, observational studies, national reports, and Gulf-region literature published between 2016 and 2025. Key thematic areas include pharmacologic mechanisms, efficacy, safety, public behaviour, affordability, off-label misuse, and policy gaps. Tirzepatide demonstrates superior glycemic and weight-loss outcomes compared to semaglutide, largely due to its dual GLP-1/GIP activity and enhanced neurobehavioral effects on appetite regulation. Semaglutide, however, retains proven cardiovascular benefits, while similar outcomes for tirzepatide await results from the ongoing SURPASS-CVOT trial. In Saudi Arabia, off-label and cosmetic use of these agents has proliferated, fueled by social media influence, inequitable access, and unregulated parallel markets. High drug costs and limited insurance coverage continue to restrict access for clinically indicated patients. Clinical audits and qualitative studies further reveal significant misuse among non-obese individuals, contributing to medication shortages and threatening equitable distribution. While GLP-1 and dual incretin therapies hold transformative potential for metabolic health, their misuse, affordability barriers, and sociocultural pressures must be addressed. National strategies involving pricing regulation, controlled prescribing policies, public awareness campaigns, and enhanced pharmacovigilance are urgently needed to optimize clinical impact and safeguard public health.